An integrated cleaner beamhouse process for minimization of nitrogen pollution in leather manufacture. (20th January 2016) - Wang, Ya-nan; Zeng, Yunhang; Zhou, Jianfei; Zhang, Wenhua; Liao, Xuepin; Shi, Bi
Abstract: Ammonia and total nitrogen are concerned wastewater pollutants generated in beamhouse processing of leather production. Nitrogen pollution in tannery wastewater is mainly originated from unhairing/liming, deliming and bating processes due to the removal of non-collagenous proteins and the use of ammonium salts. In this study, protease assisted hair saving unhairing/liming, non-ammonia deliming and non-ammonia bating were integrated into a cleaner process to minimize nitrogen impact from the origin. It was found that the performances of the integrated cleaner beamhouse process were similar or better than conventional process. Leather made by the cleaner process exhibited comparable physical and morphological properties to conventional one. Ammonia nitrogen and total nitrogen in the wastewater from the cleaner process were reduced by 97% and 48%, respectively. Meanwhile, reductions of chemical oxygen demand, total solids and sulfide were also achieved. Highlights: An integrated cleaner beamhouse process of leather production was developed. Ammonia nitrogen and total nitrogen were reduced by 97% and 48%, respectively. The quality of leather was comparable to that of conventional process.